Can social capital play a role in contracting services of family doctors in China? Refections based on an integrative review - Xu, X.; Antwi, H.A.; Boafo‑Arthur, A.; et al. (BMC Fam Pract, 2021)
Background: The family doctors’ contract service problem is not about government management alone, but an interaction of a complex social environment. Consequently, the efect of contracted services of family doctors not only depends on policy incentives but also needs to win the participation, acknowledgement, and confdence of community residents. The purpose of this integrative review is to examine whether there is any signifcant evidence that social capital in the form of social networking groups and other forms of social groups have any positive impact on the acceptance and the efectiveness of family doctors’ contractual services. Method: Research on qualitative, quantitative and hybrid methods published in peer-reviewed journals on the social capital role in the process of contract service of family doctors were eligible for inclusion. In view of the increasing attention paid to the contract service efect of family doctors during this period, a 10-year time scale was selected to ensure full coverage of relevant literature in the same period. In total, 809 articles were determined in the database retrieval results which were downloaded and transferred to the Mendeley reference application software. Results: Twelve articles met the inclusion criteria for this integrative review and the quality of the included studies were assessed using the published criteria for the critical appraisal of quantitative and qualitative research methods. Majority of the articles assessed reported that there was evidence of a positive link between social support, especially a sense of belonging and the presence of regular family doctors. The infuencing factors of patients’ contract behavior of studies conducted in China were social interaction of social capital, acceptance of the frst contact in the commu‑ nity, year of investigation, and exposure to the public. Conclusion: The study afrms previous studies that suggest that social resources have the propensity to improve relationship between patients and clients and between doctors and peers for the beneft of the patients and the stability of the overall healthcare system. Through the integration of various social resources family doctor systems accelerate the development of community construction. These social capital (social network groups) can guide resi‑ dents to use family doctor services to maintain health. Social capital can also help residents have a regular and reliable family doctor.
Research Article
Keywords: Family doctor; General practitioners; Integrative review; Social capital